Pengaruh Brand image, Shopping lifestyle, dan Live streaming Terhadap Impulse buying Pada Pengguna E-commerce Shopee Di Kalangan Mahasiswa Unisma - Navisa Ambarwati; Budi Wahono; Nanik Wahyuningtyas (UNIVERSITAS ISLAM MALANG, 2026)
Abstract The purpose of this study was to determine and analyze the influence of Brand image, Shopping lifestyle, and live streaming on Impulse buying among Shopee e-commerce users among students at the Islamic University of Malang. This study employed a quantitative method with a Likert scale as the measurement tool. The research sample was selected using a purposive sampling technique, with 85 students as respondents. Primary data were collected through an online questionnaire distributed using Google Forms. Data testing was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and coefficient of determination tests using SPSS version 26 software. The results showed that Shopping lifestyle and Live streaming had a positive and significant effect on Impulsive Buying partially, while Brand image had no significant effect partially. Simultaneously, Brand image, Shopping lifestyle, and Live streaming influenced Impulsive Buying among Shopee e-commerce users among students at the Islamic University of Malang. Keywords: Brand Image, Shopping Lifestyle, Live Streaming, Impulse Buying.